2021
DOI: 10.1038/s41467-021-21104-8
|View full text |Cite
|
Sign up to set email alerts
|

Unusual solute segregation phenomenon in coherent twin boundaries

Abstract: Interface segregation of solute atoms has a profound effect on properties of engineering alloys. The occurrence of solute segregation in coherent twin boundaries (CTBs) in Mg alloys is commonly considered to be induced by atomic size effect where solute atoms larger than Mg take extension sites and those smaller ones take compression sites in CTBs. Here we report an unusual solute segregation phenomenon in a group of Mg alloys—solute atoms larger than Mg unexpectedly segregate to compression sites of {10$$\ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(33 citation statements)
references
References 51 publications
2
31
0
Order By: Relevance
“…In contrast, coherent TBs are dislocation-free and have perfectly aligned atomic stacks, resulting in low interfacial energies compared to grain boundaries; thus, strong solute segregation is not initially expected at coherent TBs. However, several recent reports on different alloy systems have shown solute segregation along TBs and proved it is associated to the migrating heterophase interface boundary, driven by minimizing the intrinsic stacking fault, elastic strain, and/or total energy in the system 20 22 . On the other hand, it is also worth notice that solutes accumulation at the TBs can also act as Cottrell clouds surrounding the twins and thereby restrict further slip of the dislocations which was well discussed as the strength enhancement mechanism for the twinned soft materials 23 25 .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, coherent TBs are dislocation-free and have perfectly aligned atomic stacks, resulting in low interfacial energies compared to grain boundaries; thus, strong solute segregation is not initially expected at coherent TBs. However, several recent reports on different alloy systems have shown solute segregation along TBs and proved it is associated to the migrating heterophase interface boundary, driven by minimizing the intrinsic stacking fault, elastic strain, and/or total energy in the system 20 22 . On the other hand, it is also worth notice that solutes accumulation at the TBs can also act as Cottrell clouds surrounding the twins and thereby restrict further slip of the dislocations which was well discussed as the strength enhancement mechanism for the twinned soft materials 23 25 .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, coherent TBs are dislocation-free and have perfectly aligned atomic stacks, resulting in low interfacial energies compared to grain boundaries; thus, strong solute segregation is not initially expected at coherent TBs. However, several recent reports on different alloy systems have shown solute segregation along TBs and proved it is associated to the migrating heterophase interface boundary, driven by minimizing the intrinsic stacking fault, elastic strain, and/or total energy in the system [20][21][22] . On the other hand, it is also worth notice that solutes accumulation at the TBs can also act as Cottrell clouds surrounding the twins and thereby restrict further slip of the dislocations which was well discussed as the strength enhancement mechanism for the twinned soft materials [23][24][25] .…”
Section: Resultsmentioning
confidence: 99%
“…21,23−25 size larger than the matrix atom tends to take the extension site and the smaller one segregates favorably to the compression site, 21,34−37 and it can thus be understood as the larger/smaller solutes replacing the matrix atoms at the extension/ compressive sites, respectively, can minimize the strain in the lattice. However, recent results showed that larger size solutes segregated to the compression sites of {101̅ 1} TBs in Mg−Bi and Mg−Pb binary systems, 27 meaning that chemical bonding also played an indispensable role in determining the segregation behaviors. Additionally, what should be emphasized here is that the elastic strain minimization principle dominated by the atomic size effect requires that all the alternately distributed extension/compression sites in the coherent TBs should be occupied by larger/smaller solutes in an orderly and continuous manner, and all the TB 1g) and the corresponding EDS mapping images related to the elements Mg (Figure 1h), Nd (Figure 1i), and Mn (Figure 1j).…”
mentioning
confidence: 99%
“…Interfaces, including grain boundaries (GBs), phase boundaries, domain boundaries, twin boundaries (TBs), etc. , are ubiquitous crystal planar defects in materials and play a decisive role in their properties. Generally, in materials containing more than one element, the segregation of impurities/solutes at such interfaces driven by the reduction of interfacial energy can significantly alter the performances, such as cohesion, mobility, thermostability, and strength. , A typical example is the catastrophic brittle intergranular failure of metals, which is caused by the diffusion of certain elements into the boundary core. ,, The segregation behaviors at interfaces were described by the early Langmuir–McLean segregation theorem, , and it was assumed that one-layer/sub-one-layer coverage of an interface, without any solute interactions or structural transformations, nor multilayer segregation or additional solute enrichment within the bulk, e.g., precipitations, which had been demonstrated in many special interfaces, including artificial bicrystal boundaries , and coherent TBs. …”
mentioning
confidence: 99%
See 1 more Smart Citation